How Well is the Revised Common Lectionary Standing the Test of Time? - Knights, Chris H. ca. 196? (The expository times, 2019)
This article offers an evaluation of the Revised Common Lectionary (RCL) and suggests that, while it has many strengths, there are some issues with it-how common it might actually be, the repetition of some passages and the exclusion of many others, either because they contain hard material or because they are too long, the frequent use of 'Reader's Digest' abbreviated versions of texts, the designation 'semi-continuous' and the often obscure way 'related' OT lections do actually relate to the set Gospel. It concludes that, while the RCL is better than its predecessors, a slavish use of it is less than helpful.